Analisis Perkembangan Industri di Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja dimasa Pandemic Covid-19 di Nusa Tenggara Barat : - Dita Rahma; listiyana; Rita Alvin; Akung Daeng; Eka Agustiani (Jurnal Multidisiplin Madani, 2022)
The purpose of this research is to analyze the development of the number of tourism object and the number of tourists on the absorption of labor simultaneously or partially in West Nusa Tenggara during covid-19 pandemic. The method of analysis is descriptive quantitative. The tool of analysis is IMB SPSS. The result of analysis shows that partially the variabel of the number of tourism object (X1) and the number of domestic tourists (X2) has significant effect. Where the variabel of the number of tourism object has significant effect on the absorption of labor due. Simultaneously the variabel of the number of tourism object (X1) and the number of domestic tourists (X2) significantly affect.